Long-term follow-up results and complications of breast-conserving surgery using multilayer acellular dermal matrix: a retrospective study - Jung Yeol Seo; Kwang Sik Seo; Jae Woo Lee; Won Seok Oh; Seong Hwan Bae; Youn Joo Jung; Su Bong Nam (Archives of Aesthetic Plastic Surgery)
Background The advantages of using an acellular dermal matrix (ADM) for implantbased breast reconstruction in breast cancer patients are well-documented across multiple studies. However, there have been no previous instances of using multilayered ADM for reconstruction following breast-conserving surgery (BCS). This study evaluated the outcomes of breast reconstruction employing multilayered ADM for volume replacement using a local glandular flap post-BCS, and aims to underscore the advantages of this surgical approach. Methods Breast cancer patients who underwent BCS using several layers of ADM from August 2016 to December 2019 were retrospectively reviewed. Only patients with at least 3 years of follow-up were included in this study. The anticipated postoperative complications were breast deformity, seroma, hematoma, and infection. Results Seventy-four patients were included in this study. Most patients experienced symptoms of hard palpation at the reconstruction site, which indicated the surface of the ADM inserted into the breast. Ten patients developed breast deformities, accounting for 13.5% of the cases, and required surgical correction. Other complications were less frequent: four patients (5.3%) had a confirmed seroma for 6 months or longer, two patients (2.6%) experienced fat necrosis, and one patient (1.3%) underwent re-operation to remove the ADM. Conclusions Reconstruction with a glandular flap and ADM following BCS is generally simpler and requires less surgical time compared to using a latissimus dorsi flap or other local flaps. Additionally, it avoids complications at the donor site, presenting a feasible surgical alternative for BCS in breasts with small defects.